IMPACT OF DECENTRALIZATION REFORM ON THE EFFECTIVENESS OF BUDGET EXPENDITURES ON EDUCATION - Goncharenko, Maryna; Chysnevych T. (Theory and Practice of Public Administration, 2019)
The article deals with some aspects of reforming the educational management system under decentralization. The problems of the present stage of formation of united territorial communities as subjects of public management are covered. The role of local governments in implementing new approaches to the financial support mechanism for education and the role of the education sector as an indicator of the success of decentralization are emphasized. The example of the educational subvention considers new approaches to the state financial support for education, as well as the transformation of the financial mechanism of education in the context of decentralization. Attention is paid to increasing the efficiency of public spending on education in the context of limited financial resources of communities. The issues of institutional support of the quality control system of education are highlighted, the importance of centralization of quality control of education in the conditions of decentralization of powers is emphasized, as well as the necessity of cooperation between the Ministry of Education and Science, the State Service of Quality of Education and local self-government bodies in the process of managing the authorities of communities. The dynamics of the main indicators of the effectiveness of expenditures on general secondary education for 2014-2018 are analyzed using the example of Kharkiv region, certain regularities are established, in particular: the tendency of increase of the number of students is accompanied by a corresponding increase in the number of pedagogical workers with a simultaneous reduction of the network of educational institutions; the significant increase in the nominal amount of education expenditures over the last five years has been largely driven by inflationary processes in the country. The direct impact of decentralization reform on education has been proven. A number of problems of the current stage of reforming the system of public management of educational activity are identified, and suggestions for their solution are given.